Cuida e ser cuidado: compreendendo as significações desse processo para famíliares cuidadores e idosos dependentes usuários de um Centro Dia - Roque, Charles José [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Brazil has more than 20 million elderly and most of them help their families,working and/or actively participatingin the society. It is estimated that the number of people aged 60 and over,must pass from 13.8% in 2020 to 33.7% in 2060.Aging is complexanda multi-determined process involving biological, psychological, social and cultural aspects. However it is pursuedallof themto experience aging with health, autonomy and independence, a portion of thispopulation lives inafragilecondition with physical and/or cognitive limitations. This is the main target audience of the Centro de Convivência para Idosos(CCI)2 in Botucatu, São Paulo, where this research was conducted. The CCIhas professionals who provide physical, cognitive stimulation and social activities for seniors and supportinggroups andguidance to carer family.The aim of this study was to investigate the process of caring dependent older people, attending theCentro Dia, trying to understand the meanings of this process fortheseniors and for carer family. In the first stage it was performed the characterization of 75 users using the medical records of the CCI. The results showed that 79% are women; 75% are between 70 and 89 years old; 40% havelow education; 67% are widowed and80%arewhite. Seniors from this Center became dependent as a result, mainlyof Alzheimer's disease (AD) and 35% of cerebrovascular accident (CVA) 25%. Regarding comorbidities, 63% have one ortwo of them, and 38%,three or more; 65% have threeor more disability in basic activities and 100% have three or more disability in instrumental activities of daily living; 100% use of polypharmacy; 61% is caredonly by theirfamily without outsidehelp. In the second stage,semi-structured interviews were conducted with four seniors and four carer families. The analysis occurred via meaning core, based mainly in workcategories and awareness of socio-historical psychology. It was found that the process of caring is largely ...

O Brasil possui mais de 20 milhões de idosos e grande parte colabora com suas famílias, trabalha e/ou participa ativamente na sociedade. Estima-se que o número de pessoas com 60 anos e mais deve passar de 13,8%, em2020, para 33,7%, em 2060. O envelhecimento é um processo complexo e multideterminado envolvendo aspectos biológicos, psicológicos, sociais e culturais. Embora se almeje que todos vivenciem um envelhecimento com saúde, autonomia e independência,uma parcela da população vive em condição fragilizada com limitações físicas e/ou cognitivas. Esse é o principal público alvo do Centro de Convivência para Idosos (CCI) em Botucatu, interior do Estado de São Paulo, onde esta pesquisa foi desenvolvida. O CCI conta com profissionais que oferecem atividades de estimulação física, cognitiva e social para os idosos e grupos de apoio e orientações aos familiares/cuidadores. O objetivo deste estudo foi investigar o processo de cuidado àspessoas idosas com dependência, usuárias de um Centro Dia, buscando compreender as significações desse processo para idosos e familiares cuidadores. Na primeira etapa foi realizada a caracterização dos 75 usuários, utilizando-se de prontuários do CCI. Os resultados apontaram que 79% são mulheres; 75% têm entre 70 e 89 anos; 40% possuem baixa escolaridade; 67% são viúvos; 80% brancos. Os idosos desse Centro tornaram-se dependentes como consequência,principalmente,da Doença de Alzheimer (DA) 35% e de Acidente Vascular Encefálico (AVE) 25%. Quanto às comorbidades, 63% têm de uma a duas e 38% de três ou mais; 65% possuem incapacidade em três ou mais atividades básicas e 100% possuem incapacidade em três ou mais nas atividades instrumentais da vida diária; 100% fazem uso de polifarmácia; 61% é cuidado apenas pela família sem ajuda externa. Na segunda etapa foram realizadas entrevistas semiestruturadas com quatro idosos e quatro familiares cuidadores. A análise ocorreu via ...
Caring and being cared: understanding the meanigs of this process for carer family dependent elderly of a Centro Dia
Keywords: Cuidadores; Idosos - Saude mental; Psicologia social - Pesquisa; Envelhecimento - Aspectos psicológicos; Aged - Mental health; Caregivers